DIGITAL CUSTOMER EXPERIENCE AND PRICE PERCEPTION ANALYSIS ON THE TIKTOK SHOP PLATFORM: THE IMPACT ON CONSUMER LOYALTY WITH SATISFACTION AS MODERATION - Isna Damayanti; Endyastuti Pravitasari (RADJA PUBLIKA, 2026)
This study aims to analyze the influence of Digital Customer Experience and Price Perception on Consumer Loyalty on the TikTok Shop platform with Consumer Satisfaction as a moderation variable. The study uses a quantitative approach with a causality design. The research sample amounted to 110 respondents who were selected using the purposive sampling technique, namely TikTok Shop users who were at least 17 years old and had made purchases at least twice. The data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that Digital Customer Experience does not have a significant effect on Consumer Loyalty, while Price Perception and Consumer Satisfaction have a positive and significant effect on Consumer Loyalty. In addition, Consumer Satisfaction positively moderates the relationship between Digital Customer Experience and Consumer Loyalty, as well as negatively moderates the relationship between Price Perception and Consumer Loyalty, suggesting that satisfied consumers become less price-sensitive. The novelty of this study lies in testing the role of Consumer Satisfaction as a moderation variable in the context of social commerce, and shows that Digital Customer Experience has become a hygiene factor for Generation Z so that it does not directly shape consumer loyalty.